THE ROLE OF MEDIA AND COMMUNICATION IN SHAPING PUBLIC POLICY NARRATIVES ON THE ENERGY TRANSITION IN INDONESIA - Shohib Muslim; Sandra Moyo; Tafadzwa Chirwa (Yayasan Adra Karima Hubbi, 2025)
The energy transition in Indonesia represents a complex policy challenge that intertwines political will, economic interests, and environmental imperatives. Public understanding and acceptance of this transition are largely influenced by how the media and communication actors construct narratives around sustainability, fossil fuel dependency, and renewable energy adoption. This study aims to analyze the role of media and communication strategies in shaping public policy narratives and influencing stakeholder perceptions regarding Indonesia’s energy transition. A qualitative content analysis was conducted on 150 media articles, government press releases, and public statements published between 2019 and 2024, complemented by in-depth interviews with journalists, policymakers, and energy experts. The findings reveal that the Indonesian media often frames the energy transition within political and economic contexts rather than environmental urgency, leading to fragmented public understanding. Communication strategies employed by the government emphasize national development and energy sovereignty but lack consistency in sustainability messaging. The study concludes that effective and transparent communication supported by collaborative framing between media and policy institutions is essential to foster inclusive public engagement and accelerate the nation’s shift toward clean energy.